Knowledge, attitude and practice of doctors regarding perioperative tobacco smoking intervention in surgical based discipline in IIUM Medical Centre - Nanyan, Suhaila; Tengku Shaiful Bahril, Tengku Syaifa Izzura; Mohd Ikhsan, Amiratul Athirah; Ismail, Nor Hazira (Kulliyyah of Medicine, International Islamic University Malaysia, Jalan Sultan Ahmad Shah, 25200 Kuantan, Pahang, Malaysia., 2018)
Introduction: Surgery provides an exceptional chance for smoking cessation and apparently surgeons can play an important role in tobacco control. Tobacco intervention in surgical patients benefited them both in the short-term and longterm health outcome. Unfortunately, little is known about the knowledge, attitudes and practices of Malaysian surgeon regarding peri-operative tobacco smoking interventions which triggers this study. Materials and Methods: A survey of written questionnaires was conducted on medical doctors in the surgical based discipline at the International Islamic University Malaysia Medical Centre. Results: The survey response rate was 100%, and 6.7% of respondents themselves were current smoker, 23.3% were former smoker. A high proportion of respondents had accurate perceptions of peri-operative and long-term health risks of smoking. However, most of them also knew how to counsel about smoking or help patients get the help they needed to quit. Majority (93.3%) of them frequently or almost always asked about smoking status; 56.7% advised about the health risk of tobacco use; 80.0% advised patients to stop smoking peri-operatively and 60.0% advised patients to quit smoking permanently. Compared with non-smokers, smokers were significantly less likely to advice about the health risks of smoking and quitting. Not only that, most of the respondents were willing to learn about peri-operative interventions and spend an extra 5 min to help patients quit smoking. Conclusions: Majority of the respondents poised adequate knowledge of health risks of smoking, strong perception of responsibilities, and willingness to participate in tobacco control, IIUM Medical Centre doctors actually play a significant role in tobacco control in which could improve peri-operative outcomes and promote long-term health.